Enhanced electric resistivity and dielectric energy storage by vacancy defect complex - Pan, Hao (2022)
The presence of uncontrolled defects is a longstanding challenge for achieving high electric resistivity and high energy storage density in dielectric capacitors. In this study, opposite to conventional strategies to suppress de- fects, a new approach, i.e. , constructing defects with deeper energy levels, is demonstrated to address the inferior resistivity of BiFeO 3 -based dielectric films. Deep-level vacancy complexes with high charge carrier activation energies are realized via deliberate incorporation of oxygen vacancies and bismuth vacancies in low-oxygen- pressure deposited films. This method dramatically increases the resistivity by ∼4 orders of magnitude and the breakdown strength by ∼150%, leading to a ∼460% enhancement of energy density (from 14 to 79 J cm − 3 ), as well as improved efficiency and performance reliability. This work reveals the significance of rational design and precise control of defects for high-performance dielectric energy storage. The deep-level vacancy complex approach is generalizable to wide ranges of dielectric systems and functional applications.